2007
DOI: 10.2146/ajhp060220
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events involving intravenous patient-controlled analgesia

Abstract: Manufacturer-confirmed device malfunction was a major cause of reported ADE with i.v. PCA infusion pumps while operator errors were more likely to be associated with more serious adverse outcomes than device safety problems. To reduce the incidence of these problems, potential vulnerabilities in the design and manufacture of i.v. PCA pumps must be identified and addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 49 publications
1
44
1
Order By: Relevance
“…This early study took place before the 1990 change in Federal Reporting Guidelines that requires reporting of incidents involving 'device malfunctions and serious injuries or deaths' to FDA. A later study [12] found that nearly 80% of the 2009 reported incidents in 2002 and 2003 were blamed on device malfunctions and that nearly 65% of these suspected device malfunctions were confirmed by the device manufacturers. The human factors of pump interface design are an important means of reducing use errors [19,20].…”
Section: Pca Hazardsmentioning
confidence: 99%
“…This early study took place before the 1990 change in Federal Reporting Guidelines that requires reporting of incidents involving 'device malfunctions and serious injuries or deaths' to FDA. A later study [12] found that nearly 80% of the 2009 reported incidents in 2002 and 2003 were blamed on device malfunctions and that nearly 65% of these suspected device malfunctions were confirmed by the device manufacturers. The human factors of pump interface design are an important means of reducing use errors [19,20].…”
Section: Pca Hazardsmentioning
confidence: 99%
“…Errors may occur in the drug administration, usually by programming failures on infusion pump [24] and they may result in inadequate pain control, heavy sedation, respiratory depression, and, eventually, death of the patient [25]. Currently, many infusion pumps feature smart devices that are equipped with an integrated software library on dosing regimens of diferent drugs, thus avoiding underdosing or overdosing.…”
Section: Intravenous Pca (Iv-pca)mentioning
confidence: 99%
“…30 In addition, patients tended to prefer IV PCA, 30,31 which may result in greater patient satisfaction. [30][31][32][33] Although IV PCA provides no apparent decrease in cost or length of hospital stay, it does reduce demand on the nursing staff, who are required for delivery of IV or IM PRN analgesics. This reduced administration by the nursing staff may indeed have a cost benefit.…”
Section: Opioidsmentioning
confidence: 99%